CONCEPTUAL MODEL OF IMPROVING THE PROFESSIONAL-PEDAGOGICAL TRAINING OF A FUTURE PHYSICAL EDUCATION TEACHER (Universal International Scientific Journal, 2026)
This article develops and analyzes a conceptual model for improving the professional and pedagogical training of future physical education teachers on a scientific basis. The model consists of four components - theoretical and methodological basis, methodological and technological competence, practical and experimental training and reflective and developmental components, which, when integrated, form a single system. The study substantiates the central role of methodological competence, the importance of modern pedagogical technologies in physical education, and the integrative role of aesthetic education. It also highlights the importance of reflection and practical experience in developing the professional competence of future teachers.
Keywords: physical education, professional training, methodological competence, pedagogical technologies, reflection, integration, innovation, aesthetic education.